Screening of microfungi for lipolytic activity and optimization of process parameters in lipase production by solid substrate fermentation using selected microfungi (Penicillium aurantiogriseum) - Çakmak, Meltem; Aydoğdu, Halide (Kuwait Journal of Science, 2020)
In the present study, eighty-four strains of microfungi were screened for lipolytic activity. Penicillium aurantiogriseum showing high enzymatic activity among screening strains were used in fungal lipase production using solid state fermentation (SSF) method in which various agricultural wastes are used as substrates. It has been determined that the best solid substrate is sunflower pulp in SSF media where sunflower pulp, wheat bran and corn pulp is used as substrate. In addition, SSF culture media conditions for fungal lipase production were optimized. Optimum fermentation conditions were found as; 6 days of incubation time, 25oC incubation temperature, moisturizing liquid pH: 5.5 (distilled water), initial moisture level 75% (w/v), initial inoculum concentration 1 mL (1x106 spores/mL) and 1% sesame oil as carbon source. As a result of the optimum conditions, the volume activity was recorded as 0.4 U/ml and the specific enzyme activity was obtained as 1.13U/mg.